2008
DOI: 10.1038/npp.2008.175
|View full text |Cite
|
Sign up to set email alerts
|

Response Perseveration and Ventral Prefrontal Sensitivity to Reward and Punishment in Male Problem Gamblers and Smokers

Abstract: Pathological gambling (PG) is associated with maladaptive perseverative behavior, but the underlying mechanism and neural circuitry is not completely clear. Here, the hypothesis was tested that PG is characterized by response perseveration and abnormalities in reward and/or punishment sensitivity in the ventral frontostriatal circuit. Executive functioning was assessed to verify if these effects are independent of the dorsal frontostriatal circuit. A group of smokers was also included to examine whether impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
204
4
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(232 citation statements)
references
References 63 publications
19
204
4
5
Order By: Relevance
“…This observation bears relevance in the context of the recent debate questioning whether or not pathological gamblers have a hypo-active reward system (Leyton and Vezina, 2012). Whereas some studies have reported blunted brain responses to monetary rewards in pathological gamblers (Balodis et al, 2012;de Ruiter et al, 2009;Reuter et al, 2005), others have reported normal to exaggerated responses (Hewig et al, 2010;Oberg et al, 2011;Sescousse et al, 2013). Importantly, we employed an ecologically valid slot machine task with relatively high amounts of money that were delivered for real, raising confidence that our observations do not reflect a lack of behavioral relevance as has been suggested for previous studies Vezina, 2012, 2013).…”
Section: Discussionmentioning
confidence: 80%
“…This observation bears relevance in the context of the recent debate questioning whether or not pathological gamblers have a hypo-active reward system (Leyton and Vezina, 2012). Whereas some studies have reported blunted brain responses to monetary rewards in pathological gamblers (Balodis et al, 2012;de Ruiter et al, 2009;Reuter et al, 2005), others have reported normal to exaggerated responses (Hewig et al, 2010;Oberg et al, 2011;Sescousse et al, 2013). Importantly, we employed an ecologically valid slot machine task with relatively high amounts of money that were delivered for real, raising confidence that our observations do not reflect a lack of behavioral relevance as has been suggested for previous studies Vezina, 2012, 2013).…”
Section: Discussionmentioning
confidence: 80%
“…Although P as a temperament trait was paid less attention by researchers compared to other three temperaments, similar behavioral constructs such as "perseveration" (de Ruiter et al, 2009;Serpell et al, 2009) and "habit formation"/goal-directed behaviors (de Wit et al, , 2012 in humans and animals have been extensively discussed in the fields of neuropsychology, neurology, and psychiatry . Results of these studies also showed that the ventromedial prefrontal cortex played an important role in "perseveration" …”
Section: Persistencementioning
confidence: 99%
“…B. Balodis et al 2012;Romanczuk-Seiferth et al 2015;Reuter et al 2005;de Ruiter et al 2009). Zu beachten ist, dass motivationale Veränderungen des Belohnungssystems nicht gleichbedeutend sind mit Veränderungen des subjektiven Erlebens von Verstärkung bzw.…”
Section: Neurobiologische Grundlagenunclassified
“…Gleichzeitig berichten verschiedene Studien eine verminderte Reaktionsbereitschaft des Gehirns bei Personen mit pathologischem Glücksspiel auf übliche Verstärker, wie etwa Geld, Sexualität, Essen etc. (Balodis et al 2012;Reuter et al 2005;de Ruiter et al 2009 (Koehler et al 2013b;Tschernegg et al 2013;van Holst et al 2012b). Hinsichtlich möglicher hirnstruktureller Veränderungen des Gehirns bei pathologischem Glücksspiel sind die Befunde bisher wenig konsistent: Während einige Autoren keine lokalen Volumenunterschiede berichteten (Joutsa et al 2011;van Holst et al 2012a), fanden sich in anderen Studien gegenüber Gesunden erhöhte Volumina grauer Substanz im Präfrontalkortex sowie im ventralen Striatum (Koehler et al 2013a) sowie eine verringerte Integrität weißer Substanz in weiten Teilen des Gehirns pathologischer Glücksspieler (Joutsa et al 2011;Yip et al 2013).…”
Section: Neurobiologische Grundlagenunclassified